Strategi Mengurangi Pernikahan Dini melalui Peningkatan Motivasi Belajar Siswa di MTs Miftahul Ulum Kalipang Kabupaten Pasuruan - Aifi Nazili, Mazia; Moh Anshori (CV Omah Kreator, 2024)
Early marriage is a serious problem that continues to this day in Indonesia, especially in rural areas. This research was conducted with the aim of identifying and implementing strategies to reduce the rate of early marriage through a learning motivation program at MTs Miftahul Ulum, Kalipang Village, Grati District, Pasuruan Regency. This research uses descriptive qualitative methods, where data is obtained through observation, interviews and documentation. The research results show that education about the importance of education, the negative impact of early marriage, as well as changes in students' thoughts about higher education can reduce interest in early marriage. Social and economic factors such as poverty, tradition, and low parental education also play a role in influencing the decision to marry early. Mentoring and education have proven effective in increasing students' awareness of the importance of education and delaying marriage until adulthood.